2008
DOI: 10.1002/tea.20260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimenting with physical and virtual manipulatives on students' conceptual understanding in heat and temperature

Abstract: This study aimed to investigate the comparative value of experimenting with physical manipulatives (PM) in a sequential combination with virtual manipulatives (VM), with the use of PM preceding the use of VM, and of experimenting with PM alone, with respect to changes in students' conceptual understanding in the domain of heat and temperature. A pre–post‐comparison study design was used which involved 62 undergraduate students that attended an introductory course in physics. The participants were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
1
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(112 citation statements)
references
References 29 publications
3
93
1
15
Order By: Relevance
“…Mediante test conceptual y medición de tiempo de tareas entre otros, llegan a la conclusión de que el laboratorio virtual es más eficiente que el real para el aprendizaje de conceptos en electricidad. En otros estudios, Zacharia (2007), Zacharia et al (2008) y Rodríguz-Llerena y LloveraGonzález (2010) demuestran que una secuencia instruccional con entornos virtuales y reales produce mejores desempeños de los alumnos que entornos exclusivamente reales. …”
Section: Laboratoriounclassified
“…Mediante test conceptual y medición de tiempo de tareas entre otros, llegan a la conclusión de que el laboratorio virtual es más eficiente que el real para el aprendizaje de conceptos en electricidad. En otros estudios, Zacharia (2007), Zacharia et al (2008) y Rodríguz-Llerena y LloveraGonzález (2010) demuestran que una secuencia instruccional con entornos virtuales y reales produce mejores desempeños de los alumnos que entornos exclusivamente reales. …”
Section: Laboratoriounclassified
“…HENDERSON, 2005;HENDERSON;DANCY, 2009). Promover o engajamento dos alunos no processo de aprendizagem tornou-se foco de atenção de vários estudos que mostram que a aprendizagem conceitual é favorecida com métodos de ensino em que o aluno é (co)responsável por sua própria aprendizagem (HELLER et al, 1992;HAKE, 1998;ZACHARIA et al, 2008).…”
Section: Introductionunclassified
“…For many years, the natural assumption for the order of this combination had been to treat the simulation as a pre-lab exercise followed by the real laboratory experience. However, the increased benefit has been seen irrespective of the order of mode (Jaakkola & Nurmi, 2008;Zacharia, Olympiou, & Papaevripidou, 2008) and one group has even reported that the best combination in their teaching laboratory was to do the real experiment first before doing the simulation (Smith & Puntambekar, 2010).…”
Section: Introductionmentioning
confidence: 99%